APPLICATION OF WORK MOTIVATION, WORK DISCIPLINE, AND LOYALTY TO EMPLOYEE PERFORMANCE AT THE BUREAU OF FINANCE, HUMAN RESOURCES AND INFRASTRUCTURE OF IBNU SINA UNIVERSITY BATAM - Haji Mustaqim; Lukman Hakim; Suyatmi (ZILLZELL MEDIA PRIMA, 2023)
This study aims to obtain information about the relationship between the independent variables, namely; work motivation (X1), work discipline (X2), and work loyalty (X3), with the dependent variable, namely employee work performance (Y) Bureau of Finance, Human Resources and Infrastructure Facilities of Ibnu Sina University, both individually and together. The population of this study was all employees of the Bureau of Finance, Human Resources and Infrastructure of Ibnu Sina University, totaling 32 people. In this study, there was no classification of employee differences based on type or class status; both types of employment had the same treatment. Samples were taken from all existing populations, which amounted to 32 people. The results showed that there is a significant positive effect of work motivation (X1), work discipline (X2), and work loyalty (X3) on employee work performance (Y), as indicated by the Fcount value of 30.799. This value is much smaller than the Fcount value at the 0.05 alpha significance level, 2.95, or F = 30.799 < F0,05(3:28) = 2.95. Thus, it means that the better the work motivation where employees work, the higher the work discipline of employees, and the higher the work loyalty between employees, the higher the work performance of these employees. The relationship pattern of the four variables expressed by the multiple regression equation Yˆ = -11.443 + 0.497X1 + 0.079X2 + 0.937X3. Previously based on validity and reliability tests, all instruments met the validity and reliability requirements. If calculated per variable, the variable with the most influence is the work loyalty variable, which has a coefficient of determination of 64.2%. This means that job loyalty is the factor that most influence employee work performance.